Gender Differences Among Adolescent Client Evaluations of the Working Alliance in an Acute Inpatient Treatment Setting. Issue 1 (3rd July 2019) - Schmit, Erika L.; Schmit, Michael K.; Reilly, Rebecca; Fish, Matthew
ABSTRACT: Suicidal adolescents seeking treatment in inpatient hospitals benefit from a strong working alliance with their counselor to meet discharge goals. Professional counselors working in these settings should be aware of how the working alliance contributes to crisis stabilization. Using a quasi-experimental between-subjects design, we examined female and male ratings of the working alliance when working with female counselors in an acute care behavioral hospital. A statistically significant difference was found indicating that female and male adolescent clients rated the working alliance differently, with males rating it higher than females. Implications for counselor practice are discussed.